Islamic Educational Management: Case Study on Mahad Aly Baitul Qur’an, Wonogiri, Indonesia - Sunar; Sugiyo; Mufrod Teguh Mulyo; Dardiri Hasyim (LP. Ma'arif Janggan Magetan, 2022)
This article aims to observe Mahad Aly Pesantren Baitul Qur'an, Wonogiri, Indonesia, in educating students to memorize the Qur'an. We investigate Baitul Qur'an Wonogiri using educational management approach and qualitative methods to describe research findings. We lived with informants and interviewed several students, teachers, and pesantren administrators. This article argues that the management of Pesantren Baitul Quran Wonogiri has unique characteristics based on the Islamic spirit. Respect from students to teachers is the key to memorising the Qur'an quickly. In addition, the Pesantren Baitul Qur'an Wonogiri uses SWOT analysis (strength, weakness, opportunity, and threat) as a strategy to realize the vision and mission. This step is able to turn weakness dan threat into an opportunity. In articulating it, the manager includes all elements of the pesantren to get the best solution. Thus, the leadership model of pesantren has shifted from the individual to the collective. This finding is new in the study of pesantren and the management of Islamic education.